Benchmarking the Union post-Brexit: analysing the impact of Brexit on Scottish voters' attitudes towards independence - Bristow, P (2023)
Brexit has both complicated and reignited the Scottish independence debate but its effect on public opinion is uncertain. This study seeks to address this empirical question and further our understanding of support for Scottish independence by assessing the over-time effect of Brexit on independence attitudes during the Brexit negotiation period. To do this, it exploits British Election Study panel data and uses a series of change-on-change and fixed effects models to estimate the relationship between voters’ Brexit evaluations and independence attitudes over the Brexit process period. In so doing, it also investigates heterogeneity between sub-groups of Scottish voters. Its findings suggest that voters’ assessments of Brexit’s success/failure (particularly regarding its economic consequences) did influence their independence attitudes over this period. They also show that Brexit mattered most to those voters whose support in a future independence referendum will prove decisive – i.e., previously uncertain and unattached voters. This thesis attributes these findings to the “benchmarking” approach which conceptualises public opinion about constitutional change in rational, relational and dynamic terms. Using BES panel data to look through the lens of relative government performance assessments and an original online survey experiment to look through the lens of relative economic performance evaluations, it demonstrates that the “benchmarking” mechanism can be applied to the Scottish setting. Thus, it argues that the “benchmarking” approach not only serves as a useful theoretical tool to better understand the dynamics of independence support but also provides a plausible explanation for the link between Brexit and independence attitudes. In so doing, this thesis contributes to the literature on Brexit and Scottish nationalism, fills a gap in the literature regarding sub-group heterogeneity and, by applying ‘benchmark’ theory to the sub-national context, speaks to the larger literature on the dynamics of support for separatist movements within multinational states.